SUPLEMENTASI TEPUNG PORANG (Amorphophallus muelleri Blume) SEBAGAI Nutraceutical DALAM MANAJEMEN DIABETES MELLITUS TIPE 2 - Susanti, Nurlaili (El-Hayah : Jurnal Biologi, 2014)
Diabetes is a group of metabolic diseases characterized by hyperglycemia. Type 2 Diabetes is most commonly type which accounts for 90-95% of those, resulting from defects in insulin secretion and insulin action. Management of type 2 diabetes should combine pharmacological therapy with both diet modification and increasing physical activity. Nutraceutical was known to have important role. A kind of Araceae family, Porang (Amorphophallus muelleri Blume), has a main content of glucomannan. Glucomannan is a water-soluble polysaccharide, high fibers and low calories. Various studies suggest the benefit effects of glucomannan in type 2 diabetes mellitus to improve blood glucose level and lipid profiles. Its mechanism is postulated to be associated with the intrinsic physical effects of soluble fiber in the gastrointestinal tract and fermentation by microflora in the large intestine that trigger production of several gut hormones. Short Chain Fatty Acids, product of fiber fermentation, can improve insulin sensitivity through competition with free fatty acids and increasing expression of GLUT 4 in insulin sensitive tissues. Therefore, glucomannan from Porang has a great potential to be a nutraceutical for the management of type 2 diabetes mellitus.